Moral Imagination and Political Judgement: Possibilities for Empirical Research - Laima Zakaraitė (Public Policy and Administration, 2023)
The issue of morality has been addressed in politics since ancient times in numerous studies. Research in recent decades shows that the problem is still confusing and unsolved (Parrish, 2007; Bellamy, 2010; De Wijze, 2009). In a political area which is complex and dynamic, the topic of moral choice for the decision-maker remains relevant. Modern theories of organizational leadership integrate ethical aspects, taking as a starting point the cultivation of a company’s reputation or financial capital, while it is common to assume that politicians distance themselves from almost all moral values in order to act purely effectively. The article seeks a theoretical approach to research that would return the moral dimension to the realm of political decision-making. An additional supportive dimension could be an argument for the common good in order to apply a conceptual model of moral imagination to the study of the moral aspect of political decision-making. The concept of moral imagination in this aspect has already been explored in business management studies, which deconstruct and analyze the possible determinants of this concept, identifying their hypothetical connections with decision-making in the organization. Based on theoretical insights and empirical research, the conceptual model of moral imagination could also be used in the study of the decisions of politicians and political leaders.